A query-based framework to improve BIM multi-domain collaboration. Issue 10 (26th November 2021) - Sattler, Léa; Lamouri, Samir; Pellerin, Robert; Fortineau, Virginie; Larabi, Mohammed; Maigne, Thomas
ABSTRACT: Although BIM has been widely adopted in the past decade, multi-domain collaboration through BIM is still a struggle, involving different barriers such as trade-specific semantic definitions, data-schemas heterogeneousness and low levels of digital cooperation in AEC. After a brief review of existing solutions in the field and in the literature, the present paper suggests a query-based framework using BIM queries as collaborative bricks. A prototype software tool is presented that enables BIM data to be intuitively analyzed and enriched. An evaluation of 4 different use cases confirms that the suggested framework is a good candidate to enhance BIM collaboration.